Therapeutic outcomes of enzalutamide-docetaxel combination versus docetaxel monotherapy in post-sequential androgen receptor axis-targeted therapy failure metastatic castration-resistant prostate cancer - Zhiyu Zhang; Yanhang Yu; Chuanao Zhang; Jianglei Zhang; Xuefeng Zhang; Jun Ouyang (Frontiers in Oncology)
ObjectiveThis study aimed to evaluate the therapeutic efficacy and adverse effects of combining enzalutamide with docetaxel versus using docetaxel alone in treating metastatic castration-resistant prostate cancer (mCRPC) that progresses after treatment with abiraterone followed by enzalutamide.MethodsA retrospective analysis involved 67 mCRPC patients at the First Affiliated Hospital of Soochow University’s Urology Department between October 2021 and August 2023. All experienced disease progression after treatment with abiraterone and enzalutamide. Patients were either in the study group, receiving enzalutamide and docetaxel, or in the control group, treated with docetaxel alone. Prostate-specific antigen (PSA) levels, imaging changes, and common adverse reactions were compared.ResultsThe study group showed a more significant reduction in PSA levels (≥50%) and improved outcomes in bone and lymph node metastases than the control group (P < 0.05). The median PSA progression-free survival (PFS) was longer for the study group at 193 days (95% CI: 174–207) versus 127 days (95% CI: 114–160) for the control group. Similarly, the median PFS for bone metastases was 271 days (95% CI: 265–274) in the study group, compared to 185 days (95% CI: 183–265) in the control group. For lymph node metastases, PFS was 265 days (95% CI: 194–274) versus 183 days (95% CI: 180–189), respectively, all statistically significant (P < 0.05). Visual analog scale scores decreased significantly post-treatment in both groups (P < 0.05), with more pronounced pain relief in the study group; median scores were 2 (IQR, 1–3) versus 3 (IQR, 3–5; P < 0.05). No Grade 3 or higher adverse reactions occurred, although the study group had more malaise, lumbago, and backache (P < 0.05). There were no significant differences in myelosuppression, gastrointestinal issues, liver dysfunction, neurological symptoms, edema, rash, or high blood pressure between groups (P > 0.05).ConclusionCombining enzalutamide with docetaxel is more effective than docetaxel alone for treating mCRPC after abiraterone and enzalutamide, providing better PSA-PFS and improved metastasis outcomes, along with better pain relief. Though the combination resulted in more adverse effects, no severe reactions (Grade 3 or higher) were observed, indicating good tolerability and clinical potential.